Efficacy and safety of low-molecular-weight collagen peptides in knee osteoarthritis: a randomized, double-blind, placebo-controlled trial - Park, Sun-Young; Lee, Sang-Hyun; Kim, Hyun Tae; Park, Hye-Jin; Kim, Do-Un; Kim, Seung Un; Heo, In (Frontiers in Nutrition, 2025)
IntroductionKnee osteoarthritis (OA) is a common degenerative joint disease with limited safe, long-term treatment options. Nutritional interventions, such as low-molecular-weight collagen peptides (LMCP), have emerged as promising non-pharmacological strategies for joint health. However, clinical evidence is insufficient. Therefore, we aimed to assess the efficacy and safety of LMCP supplementation in patients with knee OA.MethodsIn this double-blind, randomized, placebo-controlled trial, 80 adults aged 40–75 with Kellgren–Lawrence (KL) grade I or II OA received either 3,000 mg/day LMCP or a placebo for 180 days. Primary endpoint included changes in Western Ontario and McMaster Universities Osteoarthritis (WOMAC) pain scores. Secondary endpoints included visual analog scale (VAS), WOMAC physical function and total scores, joint space width (JSW), and inflammatory markers. Adverse events (AEs) and patient compliance were monitored throughout the study.ResultsLMCP supplementation significantly reduced WOMAC pain compared to the placebo (−1.90 ± 4.14 vs. 0.61 ± 3.97; p = 0.006). Improvements in WOMAC physical function and total scores were greater in the LMCP group than in the placebo group (−4.10 ± 9.64 vs. 0.71 ± 6.47, p = 0.035; −6.24 ± 14.69 vs. −0.45 ± 9.08; p = 0.028, respectively). No significant changes were observed in JSW or inflammatory markers. No AEs occurred.ConclusionsDaily supplementation of 3,000 mg of LMCP for 180 days was safe and effective in relieving joint pain and improving function in patients with KL grade I or II knee OA. LMCP is a promising nutrition-based non-pharmacological therapeutic option, particularly for individuals seeking complementary options to long-term non-steroidal anti-inflammatory drug therapy.Clinical trial registrationThe trial was prospectively registered at the Clinical Research Information Service of South Korea (registration number: KCT0005507). The study was conducted at Pusan National University Korean Medicine Hospital (https://cris.nih.go.kr/).